Oak mildew - possibilities of its control - F. Soukup (Journal of Forest Science, 2005)
New possibilities of oak mildew (Microsphaera alphitoides) control were tested and compared with present methods. The results of three-year experiments in 6 localities (Cikar, Budkov, Planá nad Lužnicí, Vědomice, Voznice, Zadní Bor) clearly showed that the sulphur-based fungicides registered for the control of oak mildew (Sulikol K, Sulka) had a relatively good and stable effectiveness, and that two other newly tested preparations (Systhane 12 EC, Amistar) were even more effective when the percentage of infested plants did not exceed 2% (Systhane 12 EC) or 5% (Amistar) in any experimental locality. Their registration should be extended in this way. The biopreparations with fungicidal or fungistatic effects such as Supresivit, Polyversum and Ibefungin, known and used in forestry, showed that it was not possible to use them for oak mildew control, similar results were received in tentative testing of another preparation (PFR). Testing of preparations Bion 50 WG and Neem Triact 90 EC gave interesting and promising results. Besides their sufficient effectiveness in the control of oak infestation by the mildew, our experiments also indicated their generally positive influence on the health of plants; this could compensate their economic disadvantage compared to classical fungicides.